Non‐alcoholic fatty pancreas disease as a risk factor for pancreatic cancer based on endoscopic ultrasound examination among pancreatic cancer patients: A single‐center experience - Lesmana, Cosmas R A (JGH Open, 2017)
BACKGROUND AND AIM: Non‐alcoholic fatty pancreas disease (NAFPD) is a disease that ranges from simple steatosis and can further lead to chronic pancreatitis and possible pancreatic cancer development. Its exact pathogenesis and impact on clinical practice are still largely unknown. Pancreatic cancer is still the most lethal malignancy in the world. Studies about the relationship between NAFPD and pancreatic cancer are still lacking. This study aims to find the possible role of endoscopic ultrasound (EUS) examination as a screening tool in NAFPD patients based on EUS examination among pancreatic cancer patients. METHODS: EUS hospital data were collected within a 2‐year period, and all patients who underwent EUS procedures were analyzed. Pancreatic malignancy was diagnosed based on imaging and tumor markers and cytopathology using the endoscopic ultrasound fine needle aspiration (EUS‐FNA) procedure. Patients with pre‐existing pancreatic diseases, significant alcohol consumption, or other primary cancer with metastasis to the pancreas were excluded. Statistical analysis was performed using SPSS version 23.0. RESULTS: In total, 162 patients (75 females and 87 males) were recruited for database analysis.^ Pancreatic malignancy was found in 43 (26.5%) patients, whereas fatty pancreas was found in 53 (32.7%) patients, and this was commonly found among pancreatic cancer patients.^ Based on logistic regression analysis, factors such as age, gender, diabetes, and chronic pancreatitis were not found to be significant risk factors for pancreatic malignancy where fatty pancreas is the only significant risk factor for pancreatic cancer (odds ratio: 18.027 [95% CI: 7.288–44.588]). CONCLUSION: Prevalence of NAFPD among pancreatic cancer patients is high. Future studies can be conducted to show whether EUS can be considered a screening tool for the early detection of pancreatic malignancy in NAFPD patients; a cohort prospective study might also be needed to show clear causality between fatty pancreas and pancreatic cancer.